(untitled) (Research, Society and Development, 2020)
Condylar fractures are the maxillofacial fractures with greater controversy in the literature regarding forms of treatment, since, in the procedure of choice, it involves issues related to age, location and type of fracture, degree of displacement of the fractured segment, presence of other associated facial fractures, absence of teeth, restoration of dental occlusion and the time elapsed from trauma, factors that direct the choice of the type of therapeutic approach (surgical or conservative, static or functional). This study aimed to carry out an integrative review of the current literature on the treatment of condylar fractures, highlighting its indications, limitations, advantages and disadvantages. The methodology used was an integrative literature review through bibliographic research, through a search for scientific articles in the electronic database PubMed and Medline, using the keywords mandibular condyle, mandibular fractures, mandibular injuries, indexed in the period from 2015 to 2020, which dealt with cross-sectional studies, clinical and randomized trials. After the eligibility criteria, 27 articles published in English were analyzed. Studies have shown which treatment conduct brings the most safety to the intervention, presenting high reliability, allowing for predictable and rapid scientific evidence, in addition to providing treatment with lower cost and length of stay.